2014
DOI: 10.1093/her/cyu048
|View full text |Cite
|
Sign up to set email alerts
|

A content analysis of self-reported barriers and facilitators to preventing postpartum smoking relapse among a sample of current and former smokers in an underserved population

Abstract: To characterize the barriers and facilitators thatprevent postpartum relapse and maintain smoking abstinence among a socioeconomically underserved population, recruited through Philadelphia-area women, infants, and children clinics, in-person interviews were conducted with 30 women who had quit smoking for one or more pregnancies in the past 3 years to retrospectively describe their attempts to remain abstinent during the postpartum period. Responses were analysed using the constructs from the Cognitive-Social… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 53 publications
0
13
1
Order By: Relevance
“…Living in a disadvantaged community increases the likelihood of smoking due to an 'area effect' caused by highly stressful environments, limited resources and options for recreation, normalisation of smoking, increased availability of tobacco and isolation from the wider community (8)(9)(10). At an individual level, issues of nicotine addiction, competing priorities, life stress, negative attitudes towards cessation and limited access to or engagement with quit support services also influence smoking prevalence (4,(11)(12)(13)(14) Previous research has described the barriers to smoking cessation experienced by individuals living in disadvantaged areas (8,11,(15)(16)(17) and clients of community service organisations (18)(19)(20). Among the broader sphere of groups at risk of social and economic disadvantage, specific sub-populations report unique barriers to quitting (4).…”
Section: Introductionmentioning
confidence: 99%
“…Living in a disadvantaged community increases the likelihood of smoking due to an 'area effect' caused by highly stressful environments, limited resources and options for recreation, normalisation of smoking, increased availability of tobacco and isolation from the wider community (8)(9)(10). At an individual level, issues of nicotine addiction, competing priorities, life stress, negative attitudes towards cessation and limited access to or engagement with quit support services also influence smoking prevalence (4,(11)(12)(13)(14) Previous research has described the barriers to smoking cessation experienced by individuals living in disadvantaged areas (8,11,(15)(16)(17) and clients of community service organisations (18)(19)(20). Among the broader sphere of groups at risk of social and economic disadvantage, specific sub-populations report unique barriers to quitting (4).…”
Section: Introductionmentioning
confidence: 99%
“…This transition represents a unique window of opportunity for postpartum cessation since the barriers to smoking cessation have been shown to change after delivery. Decreased motivation and low social pressure to maintain abstinence, stress associated with caring for a newborn, insufficient support and resources for coping with new challenges as they arise, and postpartum depression become paramount (Curry et al, 2001; Park et al, 2009; Wen et al, 2014a, b), particularly among those who live in disadvantaged urban areas (Harmer & Memon, 2013). …”
Section: Introductionmentioning
confidence: 99%
“…Post birth women who sustained their smoking cessation held this belief for their newborn, whilst those who relapsed had lost the incentive of being pregnant. Others report similar findings, as the motivation to cease smoking in pregnancy relies upon a woman's desire to protect her unborn baby [22,37]. This motivation detracts from woman focused approaches which have greater success in sustained smoking cessation post birth [25].…”
Section: Discussionmentioning
confidence: 85%
“…Indeed, a recent thematic synthesis of 16 studies, including 1031 women, found those who relapse post birth, talk about no longer needing to protect their baby from nicotine [24]. Clinicians have been criticised for interventions which rely on this motivation, especially as a repercussion of this foetus-centric approach is reflected in the finding that post birth, women who relapse are rarely aware of the negative effects of second hand smoke [22,25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation